Men and women - next frontiers - Fogarty, Michael P.; Rapoport, Rhona; Rapoport, Robert (Economic & Social Studies, 1974)
This paper originates from the group of studies by the authors, sponsored from 1966 by PEP and the Leverhulme Trust, on Sex Career and Family, and from a series of continuing studies by them on the family, the interweaving of family life, work , and leisure, and the waste of potential among the middle-aged.
Keywords: Family life - Ireland; Work Life Balance